Intake of Vegetables, Fruits and Berries and Compliance to “Five-a-Day” in a General Norwegian Population—The Tromsø Study 2015–2016 - Nilsen, Linn; Hopstock, Laila Arnesdatter; Grimsgaard, Sameline; Carlsen, Monica Hauger; Lundblad, Marie Wasmuth (Nutrients, 2021)
Vegetables, fruits and berries are associated with reduced disease risk, and recommended intake is “five-a-day”. We studied the intake of vegetables, fruits and berries and compliance with “five-a-day” in 11,425 adults (40–96 years) who completed a food frequency questionnaire in the seventh wave of the Tromsø Study (2015–2016). Intake and proportion above/below recommended intake (250 g/day of vegetables and 250 g/day of fruits/berries, combined and separately) were analyzed. Logistic regression was used to examine compliance with recommendations in 10-year age-groups, and level of education, body mass index (BMI) and physical activity, in strata of sex and adjusted for total energy. Median intake of vegetables was 228 and 168 g/day, and fruits/berries 292 and 268 g/day, in women and men, respectively. In total, 31% of women and 17% of men met the five-a-day recommendation, and 44% and 60% of women, and 25% and 54% of men, met the recommendation for vegetables and fruits/berries, respectively. Odds of compliance with recommendation for both vegetables and fruits/berries were positively associated with age, education and physical activity ( p trend < 0.001). The intake of vegetables, fruits and berries was suboptimal, in particular for vegetables. More women than men met the recommendation, and intake varied by education, physical activity level, age and BMI.